Screening of antimicrobial activity of herbal extract of Embelia Basal, Chlorhexidine & Amoxicillin against salivary microflora of mixed dentition age group - Rahul R. Deshpande, Ankur Kulkarni, Megha Jadhav, Priyanka Mahajan, Vivian Varghese, Sucheta A. Gaikwad, Nirmala R. Deshpande (Journal of Applied Pharmaceutical Science)
The word, Ayurveda in Sanskrit roughly means the “science or knowledge of life.” Other Ayurvedic experts however, contend that Ayurveda is even more accurately translated as the “science or knowledge of longevity.” As such, it focuses on comprehensively addressing the body and preventing disease by reestablishing equilibrium. When balance is achieved, longevity – living a long, healthy, active and productive life – can be obtained(Frawley D.1989., Svoboda RE 1989). Medicinal plants represent a rich source of antimicrobial agents. Plants are used medicinally in the different countries and are a source of many potent and powerful drugs(Srivastava J et al., 1996). In this study the Antimicrobial activity of ‘Embelia Basal’ in acetone extracts were compared with Chlorhexidine and Amoxicillin 125mg and Amoxicillin 250mg against human salivary microfloraat different concentrations. The antimicrobial activity was assisted by measuring the inhibition zones by well diffusion method. Saliva was collected from children of age group 6-12 years having DMFT value four or above four. Ten salivary samples were tested for antimicrobial property to determine the Minimum Inhibition Concentration in order to increase the reliability and precision of the study. The results confirmed the antimicrobial potential of ‘Embeiia Basal’ plant at different concentrations in acetone extracts are comparable with chlorhexidine and Amoxicillin and can be used as preventive and therapeutic measure in dentistry.
Keywords: Embelia Basal, Chlorhexidine, Amoxicillin.